2013
DOI: 10.1002/14651858.cd008783.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac with or without an antiemetic for acute migraine headaches in adults

Abstract: Background This review is an update of a previously published review in Issue 2, 2012 (Derry 2012a). Migraine is a common, disabling condition and a burden for the individual, health services and society. Many sufferers choose not to, or are unable to, seek professional help and rely on over-the-counter (OTC) analgesics. Diclofenac is an established analgesic, and new formulations using the potassium or epolamine salts, which can be dissolved in water, have been developed for rapid absorption, which may be ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…9 NSAIDs.-The NSAIDs are generally a good starting point for acute migraine treatment, although acetaminophen can be tried if there are contraindications to NSAID use, and triptans are another option. Ibuprofen, 10 naproxen sodium, 11 acetylsalicylic acid (ASA), 12 and diclofenac potassium 13 all have double-blind randomized controlled trial evidence for efficacy that has been analyzed in systematic reviews. These NSAIDs have different pharmacokinetics, and this has implications for their usefulness in a specific patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 NSAIDs.-The NSAIDs are generally a good starting point for acute migraine treatment, although acetaminophen can be tried if there are contraindications to NSAID use, and triptans are another option. Ibuprofen, 10 naproxen sodium, 11 acetylsalicylic acid (ASA), 12 and diclofenac potassium 13 all have double-blind randomized controlled trial evidence for efficacy that has been analyzed in systematic reviews. These NSAIDs have different pharmacokinetics, and this has implications for their usefulness in a specific patient.…”
mentioning
confidence: 99%
“…11,19 Pharmacokinetics, dosages, and headache response rates (given as NNTs [number needed to treat]) for acetaminophen and the NSAIDs are shown in Table 1. 5,9,12,13,18,19 Combination analgesics with both acetaminophen and ASA have also been investigated for efficacy in acute migraine treatment. A combination of acetaminophen, ASA, and caffeine has been shown to have greater efficacy than any one of its components in comparable doses alone.…”
mentioning
confidence: 99%
“…A Cochrane systematic review and its update have demonstrated that ibuprofen confers relief in half of the population, but the complete disappearance of headache pain and symptoms only in a minority of migraineurs [10,11]. Additionally, diclofenac provides pain-free time only in a minority of patients [12]. Aspirin has resulted effective for acute migraine sufferers, but for the reduction of the symptoms nausea and vomiting the addition of metoclopramide 10 mg is useful [13,14].…”
Section: Not Specific Symptomatic Treatmentsmentioning
confidence: 99%
“…This drug is readily absorbed from the alimentary tract, and its half time is about one to two hours, and it will quickly dissolve in an environment with a pH higher than five. Diclofenac as one of the most potent NSAID has a few side effects when administered rectally ( 10 ). Antipyretic effects of this drug have received less attention in comparison with its analgesic effects ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%